EQONOMIC ORDER QUANTITY (EOQ) METHOD FOR INVENTORY CONTROL OF SOYBEAN RAW MATERIALS IN TOFU INDUSTRY FAUSI BONDOWOSO - Camelia, Camelia; Setianingsih, Wahyu Eko; Fatimah, Feti (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
tofu industry is an industry engaged in the food sector, namely processing agricultural products in the form of soybeans that sell food needs in the form of tofu. The process of making tofu in the Fausi tofu industry with a large amount every day makes the supply of soybean raw materials must be maintained optimally. Recording for the purchase of soybean raw materials which is still done manually by writing in a daily book makes it difficult for the owner or employees involved to review stock inventory. Descriptive analysis method with a quantitative approach is done by identifying existing data, comparing the results of the data obtained with the existing theory, producing an overview of the problem to be studied and drawing conclusions. The results of the analysis of soybean raw material inventory control in the fausi tofu industry, namely the Economic Order Quantity method can be more optimal than the manual method. Reorder point (ROP) which determines the point at which raw material inventory must be added before running out of inventory in 2023 is at least 1449 Kg. And the calculation of Total Inventory Cost in the Fausi Tofu Industry is more effective using the EOQ method than the manual method because it can reduce total inventory cost by Rp 6,710,485 so that the costs incurred are lower.